Jak (Artocarpus Integrifolla, Linn.) Plantations in Ceylon - McNeill, W. M. (Indian Forester, 1937)
The cultivation of jak has formed an important part in the planting programme of the Ceylon Forest department during the last decade. This note attempts to draw attention to the importance of the establishment of jak platations and to summarize the silvicultural knowledge which has been acquired in this connection.